Digital Depression : Information Technology and Economic Crisis - Schiller, Dan, 1951- (Book collections on Project MUSE., 2014)
"A contradiction coils through the political economy: that today's financial and economic crisis began in the historical heartland of advanced information and communications technology (ICTs): the United States. It was not supposed to turn out this way. ICTs were to be the source of economic rejuvenation and uplift. Instead, the U.S., the historical driver of digital systems and services, originated what has become the deepest and most prolonged slump since the 1930s. Today, a technological revolution is wrapped up inside an economic collapse: a digital depression. Whence did it come? Where are we headed? In Digital Depression, Dan Schiller continues his work on how networked systems and ICTs have transformed the global capitalist system. He focuses on the crisis tendencies of capitalism and confronts the contradictory matrix of technological revolution and economic stagnation that constitutes the contemporary political economy. After demonstrating digital technology's central role in the global political economy and connecting it to the rise of worldwide financial and military networks, Schiller surveys the digital communication industry before turning to the geopolitical significance of digital communication with an especially important insight on the U.S. policy apparatus and the rise of China as an oppositional force. Digital Depression demostrates that the forces at the heart of capitalism--exploitation, commodification, and inequality--along with militarization and surveillance are ongoing and accelerating within the networked political economy"--